Nonlinear dynamics of resonant tunneling optoelectronic circuits for wireless/optical interfaces - Romeira, Bruno (2012)
We report on experimental and modeling results on the nonlinear dynamics of a resonant-tunneling-diode-based(RTD) optoelectronic circuits that can be used as the basis of a wireless/optical interface for wireless access networks. The RTD-based circuits are optoelectronic integrated circuits that have negative differential resistance and act as optoelectronic voltage-controlled oscillators. These circuits display many of the features of classic nonlinear dynamics, including chaos and synchronization. These highly nonlinear oscillators behaves as injection-locked oscillators that can be synchronized by a small injection signal of either wireless or optical origin, and thus, can transfer phase encoded information from wireless to the optical domain or the optical to the wireless domain.